Soybean cultivars under the foliar application of a compounded biofertilizer in different plant phenological stages and doses - Fernando Simoni Bacilieri; Roberta Camargos de Oliveira; Ludyellen Cristina Medeiros Santos; Mara Lúcia Martins Magela; Regina Maria Quintão Lana; Ernane Miranda Lemes (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Soybean is critical in the global food scenario, and increased grain productivity and sustainability are always sought. This study evaluates the agronomic performance of soybeans with biofertilizer (BF) applications in different soybean phenological stages.Method Experiments were performed in two regions and designed in randomized blocks using a 2×4 factorial scheme (two cultivars and four BF managements). Representative plants from each parcel were used. Plant biometric variables were assessed on plants at the full bloom stage. At the beginning of grain filling, the leaf and seed biochemical components were measured. Quantitative yield components were measured at harvest.Results In both areas, the BF did not affect the soybean leaf area index, leaf dry biomass, and branch dry biomass. The BF application improved the total sugars, starch, and reducing sugars in area 1. In area 2, the chlorophyll was similar among the BF managements. Soybean cultivars and BF did not affect seed protein content in area 1. In area 2, the BF application presented a similar or greater soybean yield compared to control (no BF). The divergences observed between areas may be related to interactions between the soil-climatic conditions and the soybean cultivars.Conclusion Choosing a more appropriate soybean cultivar is fundamental to obtaining higher yields. Nutritional management with leaf-applied BF is an alternative to increase soybean field performance. However, it is still necessary to consider the interactions of the BF with the crop genetics chosen for the region of cultivation and the best dose and time of application.